A novel kind of TSV slurry with guanidine hydrochloride*Project supported by the Major National Science and Technology Special Projects (No. 2009ZX02308), the Fund Project of Hebei Provincial Department of Education, China (No. QN2014208), the Natural Science Foundation of Hebei Province, China (No. E2013202247), and Colleges and Universities Scientific research project of Hebei Province, China (No. Z2014088). (October 2015) - Hong 洪, Jiao 姣; Liu 刘, Yuling 玉岭; Zhang 张, Baoguo 保国; Niu 牛, Xinhuan 新环; Han 韩, Liying 力英
Abstract: The effect of a novel alkaline TSV (through-silicon-via) slurry with guanidine hydrochloride (GH) on CMP (chemical mechanical polishing) was investigated. The novel alkaline TSV slurry was free of any inhibitors. During the polishing process, the guanidine hydrochloride serves as an effective surface-complexing agent for TSV CMP applications, the removal rate of barrier (Ti) can be chemically controlled through tuned selectivity with respect to the removal rate of copper and dielectric, which is helpful to modifying the dishing and gaining an excellent topography performance in TSV manufacturing. In this paper, we mainly studied the working mechanism of the components of slurry and the skillful application guanidine hydrochloride in the TSV slurry.